Textualization and re-textualization: the construction of identity in South Africa - Fainman, Ronit (My University, 2015)
Thin research explores the construction of identity m Mark Behr's The Smell Of APP-lsa and Ivan Vladislav, c's BLUXLUW neranns. Both texts are written by white males who occupy positions of power within society, yet their depictions of identity differ while sharing concerns. The texts emerge from a context of Apartheid Ideology which attempted to determine identity in its creation of a social structure based on officially regulated foundational identities. Thus a theoretical framework is delineated in which to situate the operation of identity within ideological and historical formations. The Small of Annies is a subtle depiction of the construction and perpetuation of Apartheid identities despite cognisance of the violence which underlies its formation, illustrating the mechanisms which ensure that dissent is Incorporated into the dominant paradigm. M1 Fining Persona portrays identity as being as fragmented and dislocated as the social structure in which it is formed, illustrating the dissolving authority of the Apartheid system and constituting an alternative to official prescriptions of reality.